Severe endothelial injury and subsequent repair in patients after successful cardiopulmonary resuscitation - Fink, Katrin (BioMed Central, 2010)
INTRODUCTION: Ischemia and reperfusion after cardiopulmonary resuscitation (CPR) induce endothelial activation and systemic inflammatory response, resulting in post-resuscitation disease. In this study we analyzed direct markers of endothelial injury, circulating endothelial cells (CECs) and endothelial microparticles (EMPs), and endothelial progenitor cells (EPCs) as a marker of endothelial repair in patients after CPR. METHODS: First we investigated endothelial injury in 40 patients after CPR, 30 controls with stable coronary artery disease (CAD), and 9 healthy subjects, who were included to measure CECs and EMPs. In a subsequent study, endothelial repair was assessed by EPC measurement in 15 CPR, 9 CAD, and 5 healthy subjects. Blood samples were drawn immediately and 24 hours after ROSC and analyzed by flow cytometry. For all statistical analyses P < 0.05 was considered significant. RESULTS: There was a massive rise in CEC count in resuscitated patients compared to CAD (4,494.1 ± 1,246 versus 312.7 ± 41 cells/mL; P < 0.001) and healthy patients (47.5 ± 3.7 cells/mL; P < 0.0005). Patients after prolonged CPR (≥30 min) showed elevated CECs compared to those resuscitated for <30 min (6,216.6 ± 2,057 versus 2,340.9 ± 703.5 cells/mL; P = 0.13/ns). There was a significant positive correlation of CEC count with duration of CPR (R(2)= 0.84; P < 0.01). EMPs were higher immediately after CPR compared to controls (31.2 ± 5.8 versus 19.7 ± 2.4 events/μL; P = 0.12 (CAD); versus 15.0 ± 5.2 events/μL; P = 0.07 (healthy)) but did not reach significance until 24 hours after CPR (69.1 ± 12.4 versus 22.0 ± 3.0 events/μL; P < 0.005 (CAD); versus 15.4 ± 4.4 events/μL; P < 0.001 (healthy)). EPCs were significantly elevated in patients on the second day after CPR compared to CAD (1.16 ± 0.41 versus 0.02 ± 0.01% of lymphocytes; P < 0.005) and healthy (0.04 ± 0.01; P < 0.005). CONCLUSIONS: In the present study we provide evidence for a severe endothelial damage after successful CPR. Our results point to an ongoing process of endothelial injury, paralleled by a subsequent endothelial regeneration 24 hours after resuscitation.